The ‘Geological Argument’as an instrument for the acceptance of the Theory of Evolution among Greek Science Teachers - Katakos, S; Athanasiou, K (J Genet Cell Biol, 2020)
This paper examines the significance of 'geological argument' (age of earth, geological changes, stromatography, fossils) in the process of accepting the Theory of Evolution by Natural Selection (TENS), by Greek teachers that teach biology. It is a part of a wider research process, examining the conceptual ecology of evolution. That would be the most relevant terminology relating to the TENS (acceptance, understanding, opinions on the nature of science, way of thinking, religiosity) and their interconnectedness. The research was mainly quantitative, and it has been performed by the use of a closed-ended questionnaire. In addition, we used a qualitative methodology through semi-structured interviews, in order to deepen and interpret the findings of the quantitative method. The results show that there appears to occur an especially high acceptance of the TENS amongst geologists that teach biology in secondary education, compare to similar teachers of science. A finding that may lead to the conclusion that the "geological arguments" are especially strong in the process of accepting the TENS and suggest that they might, therefore, be used more often in the teaching of evolution.